Tindakan Edukatif Guru PAI dalam Mengatasi Dampak Negatif Konten Digital pada Peserta Didik - Sholihah, Al Mar’atus; Yaqin, Ainul; Saifuddin, Saifuddin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The development of digital technology has a major influence on the lives of teenagers, including the emergence of negative impacts such as social media addiction, cyberbullying, hoaxes, and declining student morale. Islamic Religious Education (PAI) teachers at SMAN 1 Puri Mojokerto have a strategic role in guiding students to be able to use digital media wisely. This study aims to: 1) Describe the negative impact of digital content on students at SMAN 1 Puri Mojokerto. 2) Describe the educational actions of PAI teachers in overcoming the negative impact of digital content. Based on its form, this study uses a qualitative approach with the type of case study research. Data collection techniques include participant observation, in-depth interviews, and documentation. Data is analyzed through three stages, namely data reduction, data presentation, and conclusion/verification. The results of the study showed: 1) The negative impact of digital content on students includes social media addiction, the spread of hoaxes, cyberbullying, declining morale, and consumptive attitudes. 2) Educational actions of PAI teachers include digital ethics guidance, counseling on the dangers of negative content, the use of exemplary methods, and approaches to religious values in the use of social media. 3) The implication of these educational actions is the increase in students' awareness in filtering information and using social media more wisely. Based on the results of the study, several recommendations can be given, namely the need to increase digital literacy in the PAI curriculum and strengthen the role of PAI teachers in shaping student character in the digital era.